KIMYO O`QITISHDA TALABALARNING IJODIY MASALALARNI YECHISHDAGI VAZIFALARI - Artikov, M.B. (SCIENCE and SOCIETY, 2023)
Creative tasks, like other tasks of natural science, are divided into experimental and theoretical. It is difficult to organize the creative process without the participation of experience. This is primarily due to the fact that experimental tasks are more attractive to students, and creativity, as mentioned above, is impossible without a great desire to solve the problem. In order to successfully form the experience of creative activity among students, each student needs criteria for choosing tasks suitable for solving . To develop such criteria, the rule about the need to form a harmonious experience of creative activity in chemical education was used. The formed individual experience can be considered harmonious if the student has solved a number of different tasks.